Determinants of fraud prevention in SMEs: The role of ethical leadership, whistleblowing system, and owner integrity - Gromyko Bongso; Vera Dumonda Silitonga; Nicholas Salim (Institute of Accounting Research and Novation (IARN), 2025)
Fraud remained a major threat to the sustainability of small and medium enterprises (SMEs), particularly due to informal control structures and limited supervision resources. This study examined the effects of ethical leadership, whistleblowing system effectiveness, and owner integrity on fraud prevention in Indonesian SMEs. A quantitative cross-sectional design was employed, and data were collected from 147 SME respondents using a structured questionnaire. The proposed model was tested using multiple linear regression in SPSS. The results showed that ethical leadership, whistleblowing system, and owner integrity had positive and statistically significant effects on fraud prevention. Among the predictors, owner integrity demonstrated the strongest influence, indicating that integrity at the top played a central role in strengthening anti-fraud practices in SMEs. The findings suggest that SMEs can enhance fraud prevention by reinforcing ethical leadership behavior, institutionalizing safe reporting mechanisms, and maintaining high integrity standards in owner decision-making. This study provided practical implications for SME governance and anti-fraud strategy development in emerging market contexts.